Structural constraints and educational development : a study of educational backwardness among tribals of Bihar : ERIC Project sponsored by N.C.E.R.T. - Sinha, Ramesh P. (A.N. Sinha Institute of Social Studies, 1996)
Study conducted in Ranchi District, India.